Tourist Satisfaction in Lombok Island as the World's Best Halal Tourism Destination - MAS’UD, Riduan; AMINY, Muhammad Muhajir; RAMADANI, Lalu Ahmad; ELBADRIATI, Baiq; YUSUP, Muhamad (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).23, 2022)
The purpose of this research is to demonstrate the connection between destination brand awareness, brand image, brand quality, and brand value in terms of improving visitor satisfaction in Lombok Island as the world’s best halal tourism destination. The researcher presents a new model and discusses the idea of a new brand value destination indicator. From the results of model testing, 250 respondents were selected using the convenience sampling technique and the WarpPLS program. The findings indicated that the study model was accepted, with an R 2 of 86.6 percent. The presented model demonstrates that the value of a destination's brand is a predictor of visitor satisfaction. The model also demonstrates that characteristics such as convenience, pricing fairness, enjoyment, and receiving advantages all contribute positively to the brand value of locations. The research's practical implications are that tourism managers should focus on and improve brand image, which currently has little impact on destination brand value, by increasing brand popularity and developing competitive advantages that can be used to convince tourists to visit tourist attractions on Lombok Island.